Scalable Deployment of React Apps using Serverless Architecture - Kumar, Akhil; Singh, Amardeep; Singh, Prabhdeep (2025 3rd International Conference on Sustainable Computing and Data Communication Systems (ICSCDS), 2025)
The increase in reliance on cloud solutions and modern web frameworks such as React.js has created a massive surge in demand for scalable and efficient web application deployment. Traditional hosting strategies are unable to handle performance, scalability, and resource utilization under fluctuating demand, which creates inefficiencies and higher costs. The issue is the challenge of serving React applications on standard server-based hosting, which often requires manual scaling, infrastructure management, and tuning. User experience is degraded with resource over-provisioning, under-provisioning, and longer load times. With Vercel, a technology that provides auto-scaling, quicker content delivery over a global CDN, and more efficient deployment processes, this article proposes serverless architecture for the deployment of React apps. The process includes optimizing React apps to serverless infrastructure, combining GitHub with Vercel for continuous deployment, and making sure traffic spikes are handled efficiently. Scalability, load time, response time, and deployment efficiency are the metrics being measured. We measure load testing, scalability testing, and response time metrics to measure the scalability of the serverless deployment. For cost savings and performance optimization, the efficiency of the proposed approach is compared to conventional server-based hosting. Our tests demonstrate that the serverless approach greatly enhances scalability and performance during busy times and decreases deployment time. Our research offers faster load times, auto-scaling, and is more efficient and cost-effective than past approaches. Based on the final findings, serverless deployment using Vercel is an efficient and scalable hosting method of new React applications with improved performance and less overhead.